Understanding Coffee Shop Consumer Preferences in Bandung: a Conjoint Analysis Approach for Nama Coffee’s Expansion - Denissa Aulia Putri; Dina Dellyana (Green Publisher Indonesia, 2025)
Nama Coffee’s expansion to Bandung requires understanding local customer preferences to ensure successful market entry and brand preference cultivation. This involves identifying key attributes influencing customer choices in Bandung’s competitive coffee shop market. This research aims to (1) identify Bandung consumer preferences for Nama Coffee’s design and concept, (2) determine the importance of coffee shop attributes in shaping these preferences, and (3) develop strategies for Nama Coffee in Bandung. This research employs a quantitative survey design, targeting Bandung coffee shop consumers. Data collection involves online and in-person questionnaires, focusing on design, facilities, menu, service, price, and promotions. Conjoint analysis will identify key preference factors and their relative importance. A TOWS matrix analyzes Nama Coffee’s internal and external environment to inform strategic recommendations. Conjoint analysis revealed